Conflict Management in Organizational Communication : Manajemen Konflik dalam Komunikasi Organisasi - Hapsari Dyah; Poppy Febriana (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to investigate the necessity of conflict management for fostering organizational health. A healthy organization not only survives environmental changes but also adapts and develops in the long term according to established visions and missions. Utilizing the In-depth Interview and documentation methods, primary and secondary data sources were employed, including literature and internet resources. The qualitative data analysis involved data reduction and presentation. Findings reveal conflicts among operators at a fuel station, specifically concerning discipline, lack of responsibility, and insufficient cooperation in scheduling holidays. Interviews with a station supervisor highlight frequent conflicts, creating discomfort in the workplace. The study suggests the need for proactive conflict resolution strategies in fuel station management to enhance overall organizational effectiveness. Highlights : Strategic Importance of Conflict Management: Effective conflict resolution strategies are crucial for sustaining organizational health and fostering adaptability amid environmental changes. Operator Dynamics in Fuel Stations: Insights into conflicts among fuel station operators, including issues related to discipline, responsibility, and collaboration in holiday scheduling. Proactive Strategies for Organizational Effectiveness: Recommendations for fuel station management to implement proactive conflict resolution measures, ensuring a harmonious and productive workplace environment Keywords: Conflict Management, Organizational Health, Fuel Station Operations, Qualitative Inquiry, Workplace Dynamics